Biosynthesis of ZnO, Bi 2 O 3 and ZnO−Bi 2 O 3 bimetallic nanoparticles and their cytotoxic and antibacterial effects - Sarani, Mina; Darroudi, Majid; Naderifar, Mahin; Akbarizadeh, Majid Reza; Nobre, Marcos A. L.; Kruppke, Benjamin; Khonakdar, Hossein Ali; Jazi, Mehdi Erfani (ChemistryOpen (Weinheim), 2024)
This work introduces an easy method for producing Bi 2 O 3 , ZnO, ZnO‐Bi 2 O 3 nanoparticles (NPs) by Biebersteinia Multifida extract. Our products have been characterized through the outcomes which recorded with using powder X‐ray diffractometry (PXRD), Raman, energy dispersive X‐ray (EDX), field emission‐scanning electron microscopy (FE‐SEM), and Fourier‐transform infrared (FT‐IR) techniques. The finding of SEM presented porous structure and spherical morphology for Bi 2 O 3 and ZnO NPs, respectively. While FE‐SEM image of bimetallic nanoparticles showed both porous and spherical morphologies for them; so that spherical particles of ZnO have sat on the porous structure of Bi 2 O 3 NPs. According to the PXRD results, the crystallite sizes of Bi 2 O 3 , ZnO and ZnO−Bi 2 O 3 NPs have been obtained 57.69, 21.93, and 43.42 nm, respectively. Antibacterial performance of NPs has been studied on Staphylococcus epidermidis and Pseudomonas aeruginosa bacteria, to distinguish the minimum microbial inhibitory concentration (MIC). Antimicrobial outcomes have showed a better effect for ZnO‐Bi 2 O 3 NPs. Besides, wondering about the cytotoxic action against cancer cell lines, the MTT results have verified the intense cytotoxic function versus breast cancer cells (MCF‐7). According to these observations, obtained products can prosper medical and biological applications.